2013
DOI: 10.1645/12-113.1
|View full text |Cite
|
Sign up to set email alerts
|

Identification ofTaeniasp. in a Natural Human Mummy (Third Century BC) from the Chehrabad Salt Mine in Iran

Abstract: Tapeworm eggs from the genus Taenia sp. were identified during the study of mummy remains dated to 2,286 ± 28 BP from the Chehrabad salt mine in northwestern Iran. The presence of tapeworm in this salt mine provides paleopathological information. Moreover, it brings new information on ancient diet, indicating the consumption of raw or undercooked meat. Cultural aspects as well as archaeozoological data are discussed in order to try to detail meat consumption. Paleoparasitological data are rare in the Middle Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…and Trichuris trichiura are often identified in archaeological deposits [ 7 , 47 50 ]. Most reports of parasite eggs in archaeological deposits either represent a small number individual skeletons or communal deposits such as latrines or waste pits [ 1 , 3 5 , 51 , 52 ]. Understanding the epidemiology of infection in past populations requires the analysis of large individual-based datasets [ 53 ] and burial-associated sediments represent a potential source of such information.…”
Section: Discussionmentioning
confidence: 99%
“…and Trichuris trichiura are often identified in archaeological deposits [ 7 , 47 50 ]. Most reports of parasite eggs in archaeological deposits either represent a small number individual skeletons or communal deposits such as latrines or waste pits [ 1 , 3 5 , 51 , 52 ]. Understanding the epidemiology of infection in past populations requires the analysis of large individual-based datasets [ 53 ] and burial-associated sediments represent a potential source of such information.…”
Section: Discussionmentioning
confidence: 99%
“…In this site, several parasitic helminth eggs were retrieved and identified, including Taenia sp. eggs in a mummified miner [22], various animal and human helminth eggs in soil samples [8], Macracanthorhynchus hirudinaceus eggs in canine paleofeces [7], and Trichosomoides crassicauda, Syphacia sp., and Trichuris sp. ova in rodent coprolites [6].…”
Section: Discussionmentioning
confidence: 99%
“…Archeological findings in Shahr-e Sukhteh have revealed that environmental condition in prehistorical time should have been more moderate than the present, due to flows of Helmand River and Hamoon Lake [22]. The presence of dicrocoeliasis may support this climatological conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Trichuris trichiura in the mummified remains of southern Siberian nomads Aufderheide 2003;Reinhard & Urban 2003;Sianto et al 2005). Natural mummies are quite rare, as specific environmental conditions are required for their preservation, such as dry climate, an oxygen-free environment, permafrost or salt mines (Fischer 1980;Aspöck et al 1996;Harter 2003;Kumm et al 2010;Nezamabadi et al 2013;Searcey et al 2013).…”
Section: Researchmentioning
confidence: 99%